Perkembangan Karier Siswa di Era Society 5.0: Studi Literatur - Efi Tri Kristiana; Evi Winingsih; Bakhrudin All Habsy (Universitas Sebelas Maret, 2026)
The rapid development of technology in the era of society 5.0 provides many new challenges and opportunities for the world of work. This transformation changes the need for workforce skills, including in the vocational education sector such as vocational schools. This research aims to explore the career development of vocational school students in the era of society 5.0 through a literature study approach. This research focuses on the technical and non-technical skills needed by vocational school students to be able to adapt to the needs of the world of work which is increasingly influenced by rapid technological advances. The research method is qualitative analysis by reviewing various related literature, including scientific articles, research reports, and vocational education policies. The research results show that skills such as digital literacy, creativity, effective communication and data analysis skills are very important in the era of society 5.0. Vocational education, especially vocational schools, is required to carry out curriculum updates that integrate technology and improve non-technical skills so that students can compete in an increasingly digitalized job market. The conclusion of this research is that the career development of vocational school students in the era of society 5.0 requires a comprehensive (holistic) approach, which includes mastery of technical and non-technical skills as well as equipping students with a strong understanding of technological developments and the latest industrial trends.